Robust and high-throughput lipidomic quantitation of human blood samples using flow injection analysis with tandem mass spectrometry for clinical use - Idkowiak, Jakub; Jirásko, Robert; Kolářová, Denisa; Bártl, Josef; Hájek, Tomáš; Antonelli, Michela; Vaňková, Zuzana; Wolrab, Denise; Hrstka, Roman; Študentová, Hana; Melichar, Bohuslav; Pešková, Karolína; et al. (Analytical and bioanalytical chemistry, 2023)
Direct infusion of lipid extracts into the ion source of a mass spectrometer is a well-established method for lipid analysis. In most cases, nanofluidic devices are used for sample introduction. However, flow injection analysis (FIA) based on sample infusion from a chromatographic pump can offer a simple alternative to shotgun-based approaches. Here, we describe important modification of a method based on FIA and tandem mass spectrometry (MS/MS). We focus on minimizing contamination of the FIA/MS both to render the lipidomic platform more robust and to increase its capacity and applicability for long-sequence measurements required in clinical applications. Robust validation of the developed method confirms its suitability for lipid quantitation in human plasma analysis. Measurements of standard human plasma reference material (NIST SRM 1950) and a set of plasma samples collected from kidney cancer patients and from healthy volunteers yielded highly similar results between FIA-MS/MS and ultra-high-performance supercritical fluid chromatography (UHPSFC)/MS, thereby demonstrating that all modifications have practically no effect on the statistical output. Newly modified FIA-MS/MS allows for the quantitation of 141 lipid species in plasma (11 major lipid classes) within 5.7 min. Finally, we tested the method in a clinical laboratory of the General University Hospital in Prague. In the clinical setting, the method capacity reached 257 samples/day. We also show similar performance of the classification models trained based on the results obtained in clinical settings and the analytical laboratory at the University of Pardubice. Together, these findings demonstrate the high potential of the modified FIA-MS/MS for application in clinical laboratories to measure plasma and serum lipid profiles.
Keywords: Lipidomics; lipidy; High-throughput lipidomics; Direct infusion lipidomics; lidé; Flow injection analysis; Lipid quantitation; Mass spectrometry; Plasma; Flow Injection Analysis; krevní plazma; tandemová hmotnostní spektrometrie; Validation; lipidomika; průtoková injekční analýza; Lipids; Tandem Mass Spectrometry; Humans